BUYINS.NET: Market Maker Surveillance Report. Highest Net Sell Volume and Negative Price Friction Stocks For February 11, 2009 (M2 Presswire, 2009)
This release contains "forward-looking statements" within the meaning of Section 27A of the Securities Act of 1933, as amended, and Section 21E the Securities Exchange Act of 1934, as amended and such forward-looking statements are made pursuant to the safe harbor provisions of the Private Securities Litigation Reform Act of 1995. "Forward-looking statements" describe future expectations, plans, results, or strategies and are generally preceded by words such as "may", "future", "plan" or "planned", "will" or "should", "expected," "anticipates", "draft", "eventually" or "projected". You are cautioned that such statements are subject to a multitude of risks and uncertainties that could cause future circumstances, events, or results to differ materially from those projected in the forward-looking statements, including the risks that actual results may differ materially from those projected in the forward-looking statements as a result of various factors, and other risks identified in a companies' annual report on Form 10-K or 10-KSB and other filings made by such company with the SEC.